Ambient humidity and the skin: the impact of air humidity in healthy and diseased states. (15th June 2016) - Goad, N.; Gawkrodger, D.J.
Abstract: Humidity, along with other climatic factors such as temperature and ultraviolet radiation, can have an important impact on the skin. Limited data suggest that external humidity influences the water content of the stratum corneum. An online literature search was conducted through Pub‐Med using combinations of the following keywords: skin, skin disease, humidity, dermatoses, dermatitis, eczema, and mist. Publications included in this review were limited to (i) studies in humans or animals, (ii) publications showing relevance to the field of dermatology, (iii) studies published in English and (iv) publications discussing humidity as an independent influence on skin function. Studies examining environmental factors as composite influences on skin health are only included where the impact of humidity on the skin is also explored in isolation of other environmental factors. A formal systematic review was not feasible for this topic due to the heterogeneity of the available research. Epidemiological studies indicated an increase in eczema with low internal (indoors) humidity and an increase in eczema with external high humidity. Other studies suggest that symptoms of dry skin appear with low humidity internal air‐conditioned environments. Murine studies determined that low humidity caused a number of changes in the skin, including the impairment of the desquamation process. Studies in humans demonstrated a reduction in transepidermal water loss (TEWL) (a measure of the integrity of the skin's barrier function) with low humidity, alterations in the water content in the stratum corneum, decreased skin elasticity and increased roughness. Intervention with a humidifying mist increased the water content of the stratum corneum. Conversely, there is some evidence that low humidity conditions can actually improve the barrier function of the skin. Ambient relative humidity has an impact on a range of parameters involved in skin health but the literature is inconclusive. Further studies are needed to better delineate the interactions that can occur in normal and diseased states. Therapeutic measures might be forthcoming especially for skin diseases such as eczema, which are regarded as being characterized by 'skin dryness'. Further research examining the interaction between different environmental exposures thought to impact the skin, and indeed the interplay between genetic, environmental and immunological influences, are required.